BMI independently relates to glycaemia in patients with severe enduring mental illness (SMI). (4th May 2017) - Anderson, Simon G; Narayanan, Ram P; Radford, Daniela; Hodgson, Richard; De Hert, Marc; Heald, Adrian H
Abstract: Background : People with severe mental illness (SMI) have higher rates of diabetes than the general population. Aims : To assess the type-2 diabetes screening rates in primary care and the relation between body mass index (BMI) and dysglycaemia for patients on the SMI register in the Cheshire region of the United Kingdom. Methods : The setting was 24 general practices in Central and Eastern Cheshire, United Kingdom. Subjects were identified through a semianonymized search of GP registers. Results : About 451 of the 787 SMI patients were screened for dysglycaemia and dyslipidaemia. Fasting glucose was in the impaired fasting glycaemia range (6.1–6.9 mmol/l) in 6.5%, and indicative of type-2 diabetes (≥7.0 mmol/l) in 17.3%. There was a positive univariate relation between BMI and fasting glucose (normalized β = 0.26, p  < 0.001). In multivariate models, adjusting for age, gender, smoking and blood pressure, each unit increase in BMI [OR = 1.07 (1.01, 1.13); p  = 0.031] and triglycerides [OR = 1.28 (1.06, 1.55); p  = 0.009] were independently associated with an increased risk of having type-2 diabetes. Conclusion : Increasing BMI relates to dysglycaemia in patients with severe enduring mental illness (SMI). All patients with SMI whether or not receiving neuroleptic treatment should undergo routine monitoring of weight and metabolic parameters.